Investigation on electroluminescence as pre-breakdown phenomenon within dielectric materials used for cable insulation - Ariffin A.M.; Tajudin N.M.; Illias H.A. (2023)
Since insulation plays a significant role in ensuring the reliability of an polymeric underground cable, many researchers across the globe are very much interested to investigate the mechanisms responsible for insulation degradation when it is subjected to high electrical stresses. One of the ways to monitor the processes leading to breakdown is by observing a phenomenon known as electroluminescence (EL) within the insulating material. This paper presents the work performed for EL monitoring in various types of dielectric materials. The measurements results obtained from previous work will be compared and discussed thoroughly in order understand better the mechanisms responsible for the occurrence in EL in dielectrics. In addition, simulation studies will also be performed based on theoretical hypotheses and the results will be compared with experimental observation. By comparing the simulation results and experimental measurements, observation of EL as a pre-breakdown phenomenon can be validated. 2012 IEEE.